Di‐tert Butyl Peroxide‐Promoted Sequential Methylation and Intramolecular Aromatization of Isonitriles. Issue 16 (6th October 2014) - Dai, Qiang; Yu, Jin‐Tao; Feng, Xiaomei; Jiang, Yan; Yang, Haitao; Cheng, Jiang
Abstract The di‐tert butyl peroxide (DTBP)‐promoted sequential reaction of isonitriles is developed, leading to 6‐methylphenanthridine derivatives in moderate to excellent yields. DTBP served as both promoter and methyl source. The procedure proceeds through the addition of a methyl radical derived from the peroxide to the isonitrile followed by aromatic homolytic cyclization. It tolerates a series of functional groups, such as fluoro, chloro, acetyl, methoxycarbonyl, cyano and trifluoromethyl. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>